2021
DOI: 10.1159/000516372
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Physician Training Level on Neonatal Tracheal Intubation Success Rates and Adverse Events: A Report from National Emergency Airway Registry for Neonates (NEAR4NEOS)

Abstract: <b><i>Introduction:</i></b> Neonatal tracheal intubation (TI) outcomes have been assessed by role, but training level may impact TI success and safety. Effect of physician training level (PTL) on the first-attempt success, adverse TI-associated events (TIAEs), and oxygen desaturation was assessed. <b><i>Methods:</i></b> Prospective cohort study in 11 international NEAR4NEOS sites between October 2014 and December 2017. Primary TIs performed by pediatric/neonatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 39 publications
4
12
0
1
Order By: Relevance
“…The top barriers to healthcare provider acceptance or adherence to change are grouped into categories, such as cognitive-behavioral, attitudinal, professional, support, and system more so than the lack of convincing evidence [ 8 ]. The attitude that an ETT is superior to LM or the professional barrier requiring physician trainees to focus on mastering intubation skills [ 9 , 10 ] would be difficult to overcome. The authors believe we have addressed many of these barriers, as also identified in the survey portion of the project, by improving LM training and awareness, increasing provider confidence in placement, and addressing organizational hurdles related to job description and availability of the device through our collaborative effort.…”
Section: Discussionmentioning
confidence: 99%
“…The top barriers to healthcare provider acceptance or adherence to change are grouped into categories, such as cognitive-behavioral, attitudinal, professional, support, and system more so than the lack of convincing evidence [ 8 ]. The attitude that an ETT is superior to LM or the professional barrier requiring physician trainees to focus on mastering intubation skills [ 9 , 10 ] would be difficult to overcome. The authors believe we have addressed many of these barriers, as also identified in the survey portion of the project, by improving LM training and awareness, increasing provider confidence in placement, and addressing organizational hurdles related to job description and availability of the device through our collaborative effort.…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal intubation is an essential procedure that all neonatologists need to be competent and proficient in performing. The procedure in this population is complicated not just by the small size of the baby but also by the unique physiology of the newb,orn which leads to decreased reserve and less apnoeic tolerance during laryngoscopy 10–16. As infants are surviving at lower gestational ages and birth weights than before, the procedure is only likely to become more challenging.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure in this population is complicated not just by the small size of the baby but also by the unique physiology of the newb,orn which leads to decreased reserve and less apnoeic tolerance during laryngoscopy. [10][11][12][13][14][15][16] As infants are surviving at lower gestational ages and birth weights than before, the procedure is only likely to become more challenging. As the difficulty increases, procedural experience is decreasing due to greater use of non-invasive ventilation, a reduction in working hours and significantly increased numbers of not just trainees but also consultants.…”
Section: Discussionmentioning
confidence: 99%
“…In this workshop, we used the incubator (Giraffe Incubator Carestation, GE Healthcare, United States) ventilator (Dräger Babylog® VN500), manikin (Premature Anne, Laerdal Medical), and all the other equipment used in the neonatal resuscitation program course. This workshop has a didactic session with video materials, a complex timed preterm inter-professional resuscitation scenario using a medium-fidelity manikin, followed by a post-resuscitation team debriefing ( 18 , 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…It is important to mention that most of our tracheal intubations are performed by neonatal-perinatal fellows and advanced neonatal providers e.g., specialists and consultants rather than the trainee paediatric residents. This explains the gradual decrease in opportunities for trainee paediatric residents to perform tracheal intubation in their neonatology rotations ( 19 ).…”
Section: Program Impacts On Clinical Practisementioning
confidence: 99%